2023
DOI: 10.3390/molecules28041672
|View full text |Cite
|
Sign up to set email alerts
|

How to Regulate the Migration Ability of Emulsions in Micro-Scale Pores: Droplet Size or Membrane Strength?

Abstract: Micro visualization has become an important means of solving colloid and interface scientific problems in enhanced oil recovery. It can establish a relationship between a series of performance evaluations of an oil-water interface under macroscopic dimensions and the actual application effect in confined space, and more truly and reliably reflect the starting and migration behavior of crude oil or emulsion in rock pores. In this article, zwitterionic surfactant alkyl sulfobetaine (ASB) and anionic extended sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, there is also a kinetic mechanism for anionic surfactants increasing the three-phase contact angle. Sun et al [ 32 ] found that the contact angle of crude oil in anionic surfactants was higher than that in simulated water through macroscopic oil–water–solid contact angle experiments. The results indicated that the surfactant molecules adsorbed at the oil–water interface and solid surface, and generated separation pressure at the three-phase contact point through electrostatic repulsion, which enhanced their ability to strip the oil film on the solid surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is also a kinetic mechanism for anionic surfactants increasing the three-phase contact angle. Sun et al [ 32 ] found that the contact angle of crude oil in anionic surfactants was higher than that in simulated water through macroscopic oil–water–solid contact angle experiments. The results indicated that the surfactant molecules adsorbed at the oil–water interface and solid surface, and generated separation pressure at the three-phase contact point through electrostatic repulsion, which enhanced their ability to strip the oil film on the solid surface.…”
Section: Resultsmentioning
confidence: 99%
“…O-linked glycosylation often occurs in the Golgi and Endoplasmic Reticulum [6]. O-glycans are generated by adding Nacetylgalactosamine (GalNAc), N-acetylglucosamine, fucose, glucose, xylose, mannose, or galactose to serine (Ser) and threonine (Thr) residues of proteins [7]. O-GalNAc glycosylation (Mucin-type Oglycosylation) is initiated by a family of 20 homologous genes encoding polypeptide GalNActransferases (ppGALNTs), and the enzymatic process is initiated in in the Golgi [6,8].…”
Section: Introductionmentioning
confidence: 99%